2012
DOI: 10.1002/adma.201202397
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Exciton Dissociation in Singlet Exciton Fission Photovoltaics

Abstract: Triplet exciton dissociation in singlet exciton fission devices with three classes of acceptors are characterized: fullerenes, perylene diimides, and PbS and PbSe colloidal nanocrystals. Using photocurrent spectroscopy and a magnetic field probe it is found that colloidal PbSe nanocrystals are the most promising acceptors, capable of efficient triplet exciton dissociation and long wavelength absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
152
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(160 citation statements)
references
References 35 publications
8
152
0
Order By: Relevance
“…The magnitude of the magnetic field effect can measure the efficiency of exciton fission and its competition with loss processes [7,11]. The sign of the effect demonstrates whether a device output is dominated by singlet or triplet excitons [11,12]. For example, the effect on photocurrent in a solar cell is negative if that device generates charge from triplet excitons, but positive if it instead generates charge mostly from singlet excitons [12].…”
mentioning
confidence: 99%
“…The magnitude of the magnetic field effect can measure the efficiency of exciton fission and its competition with loss processes [7,11]. The sign of the effect demonstrates whether a device output is dominated by singlet or triplet excitons [11,12]. For example, the effect on photocurrent in a solar cell is negative if that device generates charge from triplet excitons, but positive if it instead generates charge mostly from singlet excitons [12].…”
mentioning
confidence: 99%
“…24 In addition, the excitons generated in regions with different stacking directions may have varying dissociation efficiencies as the charge transfer state energy of the pentacene/C 60 molecular couple is minimized for the configuration, where the short molecular axis of pentacene is interfaced with C 60 . 25 Furthermore, because the pentacene crystal diameter in our films (250 6 100 nm, obtained with atomic force microscopy) is comparable to the wavelength of incident light, we may need to consider two separated polarization phases each with its own optical constants and generation profiles. Ellipsometry measurements on pentacene single crystals described in Ref.…”
mentioning
confidence: 99%
“…Singlet fission is particularly attractive because of the high quantum efficiency (B200%, triplet excitons per photon) in a few well-known organic semiconductors, such as pentacene and Tc, and the prospect of designing and synthesizing new singlet fission molecules 3,4 . Although several research groups have demonstrated solar cells and photodetectors using singlet fission materials [5][6][7][8][9][10] , we are far from understanding how to efficiently harvest singlet fission for enhanced solar energy conversion. Design principles for molecules with high singlet fission yields are starting to emerge 3,4 but little is known about how to optimally extract the two electron-hole pairs resulting from singlet fission.…”
mentioning
confidence: 99%
“…One strategy of harvesting singlet fission for solar energy conversion is to form an interface between a singlet fission material (for example, Tc or pentacene) and an electron acceptor (for example, fullerene or inorganic semiconductor quantum dots) for multiple CT (refs [5][6][7][8][9][10]. A limitation of this approach is that CT processes from both the singlet and the triplet pair are possible 11 ; the former does not contribute to any increase in power conversion efficiency beyond the ShockleyQueisser limit and is difficult to avoid for most electron acceptors.…”
mentioning
confidence: 99%